El Impacto de las medidas arancelarias en los indicadores financieros de los sectores económicos del Ecuador, periodo 2010-2015. - Ron Puente, Jennifer Stephania (2017)
This investigation is about tariff policy and their impact on the financial indicators of the economic sectors of Ecuador in the period 2010-2015, the main objective is the impact of tariff policy on the financial indicators of the economic sectors, in order to achieve the purpose, several aspects were considered, the behavior of the tariff policy implemented for the productive and commercial sectors and the evolution of the financial indicators Besides, the information of each indicator and variable is compiled by tables for every analysis and interpretation. This investigation contains formulation of the problem, the general and specific objectives, and the objectives to be fulfilled demonstrate the importance of the investigation. The Theoretical Framework contains concepts, characteristics, and theories, which support the behavior of Ecuador's tariff policy, and also the objectives and instruments used to implement it. The methodology, in this investigation features the analysis of the data of several economic sectors for the implementation tariff policy that allow demonstrating the incidence and the behavior from both. Finally, we present the conclusions and recommendations of the investigation after analyzing and interpreting the data collected through which we can make new forms of decision-making and behavior for each sectors.